(untitled) (Research, Society and Development, 2022)
Autism Spectrum Disorder (ASD) consists of a group of neurological development disorders and affects, globally, approximately 1 in every 160 children. Motor disorders are found in up to 79% of individuals with autism, and are correlated with language performance and social behavior. This study sought to answer the following question: Can motor skills be correlated with the development of expressive language in autism? The search was carried out in the Scielo, Pubmed, Lilacs, Scopus and Web Of Science databases. Terms in English, standardized and extracted from the Health Sciences Descriptors (DECS) and the Medical Subject Headings (MeSH) were used. Original articles published in national and international journals from 2015 to 2020, in English and Portuguese, were included. The search resulted in 12,822 articles, including 7 articles after selection. The paths taken to the development and manifestation of motor and language deficits in autism still constitute a gap for science, however, the scientific literature explored allows for the establishment of a potential bilateral interference relationship between these factors, allowing the expansion of the universe of investigations. in the motor approach to these deficits.